2019
DOI: 10.1021/acs.est.9b02736
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Metabolomics for Untargeted Screening and Prioritization of Vertebrate-Active Stressors in Streams Across the United States

Abstract: The U.S. Geological Survey and the U.S. Environmental Protection Agency have assessed contaminants in 38 streams across the U.S., using an extensive suite of target-chemical analysis methods along with a variety of biological effects tools. Here, we report zebrafish liver (ZFL) cell-culture based NMR metabolomic analysis of these split stream samples. We used this untargeted approach to evaluate the sites according to overall impact on the ZFL metabolome and found that neither the total number of organics dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…One approach involves studying changes in specific metabolites or suites of metabolites to identify biological pathways affected by a given individual test chemical (e.g., Collette et al 2010; Ekman et al 2012; Davis et al 2017). The second approach employs changes in metabolite profiles to provide inferences about the nature of the complex chemical mixture associated with observed biological effects (e.g., Davis et al 2013, 2016; Collette et al 2019). As an illustration of this second type of application, Davis et al (2013) described a caged fish study in which comparative metabolite profiles enabled definition of the contribution of pulp and paper mill influent to the biological effects of a WWTP effluent by conducting measurements in fish exposed before, during, and after a scheduled shutdown of the mill.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One approach involves studying changes in specific metabolites or suites of metabolites to identify biological pathways affected by a given individual test chemical (e.g., Collette et al 2010; Ekman et al 2012; Davis et al 2017). The second approach employs changes in metabolite profiles to provide inferences about the nature of the complex chemical mixture associated with observed biological effects (e.g., Davis et al 2013, 2016; Collette et al 2019). As an illustration of this second type of application, Davis et al (2013) described a caged fish study in which comparative metabolite profiles enabled definition of the contribution of pulp and paper mill influent to the biological effects of a WWTP effluent by conducting measurements in fish exposed before, during, and after a scheduled shutdown of the mill.…”
Section: Discussionmentioning
confidence: 99%
“…As an illustration of this second type of application, Davis et al (2013) described a caged fish study in which comparative metabolite profiles enabled definition of the contribution of pulp and paper mill influent to the biological effects of a WWTP effluent by conducting measurements in fish exposed before, during, and after a scheduled shutdown of the mill. To build on this approach, we subsequently developed a more direct way to associate changes in endogenous metabolite profiles with individual contaminants in complex mixtures using PLS regression (Davis et al 2016; Collette et al 2019). For the present study, we employed this PLS‐based method to identify contaminants in the measured mixtures that covaried with hepatic metabolomic changes, to highlight (or possibly eliminate) chemicals of potential concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The eco-exposome concept-Environmental Toxicology and Chemistry, 2022;41:30-45 eco-and human exposome research (Collette et al, 2019;Jeong et al, 2018;Rappaport, 2012;Zheng et al, 2020). For example, Collette et al (2019) used PLS combined with crossvalidated predictive residuals analyses to identify stressors related to endogenous metabolite profiles in a zebrafish cell line exposed to water sample extracts from 38 different US streams.…”
Section: Making the Link Between Exposure And Effectmentioning
confidence: 99%
“…The ZFL cell line was chosen due to the extensive use of zebrafish as a model for both human and ecological health-related toxicological research 18 and its demonstrated use for monitoring biological effects of complex mixtures of contaminants in surface water. 19 We sought first to assess the potential of the ZFL lipidome for environmental monitoring and, second, to identify potentially useful lipid-based biomarkers for identifying adverse cellular and subcellular effects.…”
Section: ■ Introductionmentioning
confidence: 99%